Acute toxicity of a commercial glyphosate formulation on European sea bass juveniles (Dicentrarchus labrax L.): gene expressions of heme oxygenase-1 (ho-1), acetylcholinesterase (AChE) and aromatases (cyp19a and cyp19b). - Prevot-D’Alvise, N.; Richard, S.; Coupé, S.; Bunet, R.; Grillasca, J P. (Cellular and Molecular Biology, 2013)
Acute toxicity of Roundup, a commercial glyphosate-based herbicide, was evaluated in a teleost marine fish, the European sea bass, after 96h of exposure. The LC50 96-h value of Roundup was 529 mg/L. Juveniles (Dicentrarchus labrax L.) were exposed to a sublethal concentration (35% of the LC50, i.e. 193 mg/L) of Roundup for 96-h. The study of heme oxygenase-1 (ho-1) gene expression was performed in four tissues (liver, gills, brain and gonads) and highlighted the disruption of antioxidant defence system. Results showed that ho-1 mRNA levels in liver and gills significantly decreased (p<0.001 and p<0.01 respectively) in fish exposed to 193 mg/L of Roundup, whereas in brain and gonads, ho-1 mRNA level was not altered. The analysis of acetylcholinesterase expression was used to evaluate the overall neurotoxicity of the herbicide and aromatase genes to assess the alteration of the endocrine system. Results showed that AChE and cyp19b gene transcriptions significantly increased (p<0.01) in brain of sea bass, whereas aromatase gene expression (cyp19a) in gonads was not significantly altered. Our results showed complex tissue-specific transcriptional responses after 96h of exposure to a sublethal concentration. All these disruptions confirmed the deleterious effects of this glyphosate-based herbicide in a marine species.